The Effect of Compensation on Employee Turnover Intention at MSMEs in Denpasar City: Job Satisfaction as Mediation - I Putu Agus Adi Wiguna; Ida Ayu Putu Widani Sugianingrat; I Made Astrama (UNHI Press, 2023)
Purpose – HR problems in MSMEs need special attention because they have an impact on the development of the business and also contribute to the government. The purpose of this study was to analyse the effect of compensation on turnover intention through job satisfaction. Methodology – The research used an explanatory approach with quantitative methods. The research population is employees in the culinary sector MSMEs in Denpasar City. The number of samples in this study using the Lemeshow formula with a total of 96 people determined using purposive sampling. The research instrument used a questionnaire and the data analysis technique was inferential with Structural Equation Model-Partial Least Square (SEM-PLS) analysis. Findings – The results showed that compensation affects turnover intention directly or through mediation of job satisfaction. This applies to employees of culinary sector MSMEs in Denpasar City. Originality – MSMEs managers are expected to always follow the policy of compensating employees and also evaluate the compensation policy and provide information to employees regarding the compensation assessment system so that there is satisfaction in employees.